Beauty Care Kebutuhan Kultural Perempuan Metropolitan - Ivada, Denisa; Restu Darmawan, Diaz; Novianti, Nadia (Humanis; Vol 26 No 3 (2022)DO - 10.24843/JH.2022.v26.i03.p02, 2022)
This paper discusses the cultural phenomenon of urban women in the modern era that gives rise to a lifestyle in an effort to maintain health. The lives of women in urban areas have a need to take care of skin health. One way to treat it is to buy beauty care products or skincare. The behavior that appears with a variety of beauty and skincare products makes it a cultural necessity. The emergence of dependence on beauty clinics and various beauty products cannot be separated from the identity of women in urban areas. This paper is based on the results of a qualitative research method with a phenomenological approach. Based on key informants the knowledge and needs of skin health are influenced by the media and popular culture. The need for skin health through skincare products affects the beauty standards of modern women in urban areas.